Apolipoprotein E4 Effects a Distinct Transcriptomic Profile and Dendritic Arbor Characteristics in Hippocampal Neurons Cultured in vitro - Diaz, Jenny R.; Martá-Ariza, Mitchell; Khodadadi-Jamayran, Alireza; Heguy, Adriana; Tsirigos, Aristotelis; Pankiewicz, Joanna E.; Sullivan, Patrick M.; Sadowski, Martin J. (Frontiers in Aging Neuroscience, 2022)
The APOE gene is diversified by three alleles ε2, ε3, and ε4 encoding corresponding apolipoprotein (apo) E isoforms. Possession of the ε4 allele is signified by increased risks of age-related cognitive decline, Alzheimer’s disease (AD), and the rate of AD dementia progression. ApoE is secreted by astrocytes as high-density lipoprotein-like particles and these are internalized by neurons upon binding to neuron-expressed apoE receptors. ApoE isoforms differentially engage neuronal plasticity through poorly understood mechanisms. We examined here the effects of native apoE lipoproteins produced by immortalized astrocytes homozygous for ε2, ε3, and ε4 alleles on the maturation and the transcriptomic profile of primary hippocampal neurons. Control neurons were grown in the presence of conditioned media from Apoe-/- astrocytes. ApoE2 and apoE3 significantly increase the dendritic arbor branching, the combined neurite length, and the total arbor surface of the hippocampal neurons, while apoE4 fails to produce similar effects and even significantly reduces the combined neurite length compared to the control. ApoE lipoproteins show no systemic effect on dendritic spine density, yet apoE2 and apoE3 increase the mature spines fraction, while apoE4 increases the immature spine fraction. This is associated with opposing effects of apoE2 or apoE3 and apoE4 on the expression of NR1 NMDA receptor subunit and PSD95. There are 1,062 genes differentially expressed across neurons cultured in the presence of apoE lipoproteins compared to the control. KEGG enrichment and gene ontology analyses show apoE2 and apoE3 commonly activate expression of genes involved in neurite branching, and synaptic signaling. In contrast, apoE4 cultured neurons show upregulation of genes related to the glycolipid metabolism, which are involved in dendritic spine turnover, and those which are usually silent in neurons and are related to cell cycle and DNA repair. In conclusion, our work reveals that lipoprotein particles comprised of various apoE isoforms differentially regulate various neuronal arbor characteristics through interaction with neuronal transcriptome. ApoE4 produces a functionally distinct transcriptomic profile, which is associated with attenuated neuronal development. Differential regulation of neuronal transcriptome by apoE isoforms is a newly identified biological mechanism, which has both implication in the development and aging of the CNS.